Peran keluarga dalam membentuk karakter keislaman siswa kelas 9 di SMP IT Nurul Iman Pesawaran - Pratama, Syahriza Ariyo; Khoironi; Rohili, Thahir (Program Studi Magister Pendidikan Agama Islam, 2025)
This research will discuss the role of the family in shaping the Islamic character of grade 9 students at SMP IT Nurul Iman Pesawaran. Against the background of the adolescent moral crisis in the era of globalization, this research aims to understand family efforts in educating children's Islamic values. Using qualitative methods includes observation, interviews and documentation. The research results indicate that the family has an important role through example, habitual worship, and open communication. Congregational prayer activities, reciting the Koran, and moral learning must also be implemented regularly. The obstacles for parents in educating their children's character are limited time, the influence of technology, and an unsupportive environment. The solution that can be taken is collaboration between families, schools and religious communities to create a good environment for the formation of children's Islamic character. This research provides insight for parents and educational institutions to form a young generation with Islamic character who is ready to face changing times. Abstrak Penelitian ini akan membahas peran keluarga dalam membentuk karakter keislaman siswa kelas 9 di SMP IT Nurul Iman Pesawaran. Yang dilatar belakangi krisis akhlak remaja di era globalisasi, Penelitian ini bertujuan memahami upaya keluarga dalam mendidik nilai-nilai islami anak. Menggunakan metode kualitatif mencakup observasi, wawancara, dan dokumentasi. Hasil penelitian mengindikasikan keluarga memiliki peran yang penting melalui teladan, pembiasaan ibadah, dan komunikasi terbuka. Kegiatan shalat berjamaah, mengaji, dan pembelajaran akhlak juga harus di terapkan secara rutin. Kendala orang tua dalam mendidik karakter anak adalah keterbatasan waktu, pengaruh teknologi, dan lingkungan yang kurang mendukung. Solusi yang bisa di ambil ialah kolaborasi antara keluarga, sekolah, dan komunitas keagamaan guna menciptakan lingkungan yang baik untuk pembentukan karakter islami anak. Penelitian ini memberikan wawasan bagi orang tua dan Lembaga pendidikan guna membentuk generasi muda yang berkarakter islami yang siap menghadapi perubahan zaman.